PENINGKATAN DAYA SAING UMKM MINUMAN OLAHAN KOPI MELALUI STRATEGI BRANDING (STUDI KASUS: LASKAR KOPI ARJASARI) - Lukito, Wahyu (Visualita Jurnal Online Desain Komunikasi Visual, 2021)
The increasing number of MSMEs in the Bandung area, especially in the field of processed coffee drinks, has resulted in increased competition among business actors. This competition creates problems for MSMEs to develop. Apart from experiencing one of these external problems, MSMEs also have internal problems. The majority of internal problems experienced by MSMEs are in terms of marketing. From these problems, a study is needed to analyze and formulate a branding strategy through visual identity, to increase the competitiveness of coffee-processed beverages MSME which is the object of research. This study uses a qualitative phenomenological approach, by conducting research methods of literature study, observation and interviews. It is hoped that by carrying out this analytical study the relevant stakeholders, both business actors and designers, will make this research a reference in determining the right, effective and efficient branding strategy for MSMEs. The strategy that can be done is the focus of differentiation. The results achieved, Laskar Kopi Arjasari can focus on developing product values ​​and optimizing its brand identity. Laskar Kopi Arjasari brand identity can be optimized by implementing it in promotional media, both offline promotion media and online promotion media.